-6x-78=57-x

Simple and best practice solution for -6x-78=57-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-78=57-x equation:


Simplifying
-6x + -78 = 57 + -1x

Reorder the terms:
-78 + -6x = 57 + -1x

Solving
-78 + -6x = 57 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-78 + -6x + x = 57 + -1x + x

Combine like terms: -6x + x = -5x
-78 + -5x = 57 + -1x + x

Combine like terms: -1x + x = 0
-78 + -5x = 57 + 0
-78 + -5x = 57

Add '78' to each side of the equation.
-78 + 78 + -5x = 57 + 78

Combine like terms: -78 + 78 = 0
0 + -5x = 57 + 78
-5x = 57 + 78

Combine like terms: 57 + 78 = 135
-5x = 135

Divide each side by '-5'.
x = -27

Simplifying
x = -27

See similar equations:

| 10=6y+2+3y+17 | | 4+3+2+6+10= | | 4(x-1)=5.6 | | 2(m-22)+3(m-4)=36 | | 1.4(5x-0.2)= | | x+-39=-2x+33 | | 25(2x^2+11x-18)=0 | | z-39=-2x+33 | | 40-5w=3w | | 2e-5=-4.6 | | 5x+(-x)= | | 3n-7n+12=32 | | 6z=16 | | 19.8x=91 | | 50x^2+275x-450=0 | | -51+6x=84+11x | | 9(s+3)-34= | | 4x-6x+x-9x= | | -2a+-9=6a+13 | | 3x-7+9-2x=x+1 | | -2a-9=6a+143 | | -42-6x=x+70 | | 4x-5x+2x-6x= | | -6x-18=8-7x | | 4x+13+15x+15=180 | | 2.5-0.02x=1.08 | | -3+46=8x+4-5x | | 2+-4y=10 | | 5x-17=9+7x | | 4a=4a+6 | | 45-[5+7y-2(y+4)]=-5(4y-3)-[9(y-1)-16y+8] | | 3/4g+2.5=4/3g-2.4 |

Equations solver categories